Pro SQL Server 2008 XML - Coles, Michael (Apress, 2012)
This book provides detailed information on XML from the SQL Server 2008 perspective. I’ll discuss several aspects of SQL Server 2008 XML, including the XML functionality built right into SQL Server, as well as how to access SQL Server functionality that is not built into T-SQL. I’ll even look at client-side XML technologies that are important to SQL Server/XML–based application design. In all, I hope you find this book enjoyable and useful in designing and mplementing your own SQL Server and XML-based applications.